Observation of the [Lambda]0b→ J[psi]/[Xi]−K+ and [Xi]0b→ J/[psi][Xi]−π+ decays - Aaij, Roel; Bachmann, Sebastian; Carus, Leon; Caspary, Rowina; Celani, Sara; Cocha Toapaxi, Carlos; De Cian, Michel; Dittmann, Lucas; Esen, Sevda; Glaser, Fabian; Günther, Paul André; Han, Xiaoxue; et al. (The European physical journal. C, Particles and fields, 2025)
The first observation of the Ξ0b → J/ψΞ−π+ decay and the most precise measurement of the branching fraction of the Λ0b → J/ψΞ−K+ decay are reported, using proton-proton collision data from the LHCb experiment collected in 2016–2018 at a centre-of-mass energy of 13TeV, corresponding to an integrated luminosity of 5.4 fb−1. Using the Λ0b → J/ψΛ and Ξ−b → J/ψΞ− decays as normalisation channels, the ratios of branching fractions are measured to be B(Λ0b → J/ψΞ−K+) B(Λ0b → J/ψΛ) = (1.17 ± 0.14 ± 0.08) × 10−2 , B(Ξ0b → J/ψΞ−π+) B(Ξ−b → J/ψΞ−) = (11.9 ± 1.4 ± 0.6) × 10−2, where the first uncertainty is statistical and the second systematic.
Online veröffentlicht: 28. Juli 2025
Im Titel sind die Zahl 0 sowie die Plus- und Minuszeichen hochgestellt
Im Titel ist der Buchstabe "b" tiefgestellt
*LHCb Collaboration: R. Aaij, S. Bachmann, L. Carus, R. Caspary, S. Celani, C. Cocha Toapaxi, M. De Cian, L. Dittmann, S. Esen, F.C. Glaser, P.A. Günther, X. Han, S. Hansmann-Menzemer, P. Herrero Gascon, C. Langenbruch, B. Leverington, J. Marks, M.P. Morgenthaler, S.R. Roy, M. Ruiz Diaz, M.D. Tat, G. Tuci, L.H. Uecker, D.J. Unverzagt, U. Uwer, C. Wang, L. Witola, Y. Zhao, A. Zhelezov [und sehr viele weitere Personen]
Gesehen am 07.01.2026